Lithium in Chile: Present Status and Future Outlook - Ruiz-Leon, D; Ruiz-Leon, D (Royal Society of Chemistry, 2024)
This paper provides a comprehensive overview of the current state of lithium in Chile, with a forward-looking assessment in the context of the ongoing national lithium strategy. The global and regional significance of lithium as a critical energy resource is examined. The evolution of Chile s lithium industry is analyzed, emphasizing two recent key policy initiatives: the 2015 National Lithium Commission report and the newly launched national lithium strategy. The salient features of these initiatives are outlined. Additionally, this paper reviews materials science research conducted in Chile since the 1960s, particularly focusing on the physical chemistry of lithium, batteries and brines. Finally, the paper argues that lithium, as a pivotal material in the shift from fossil fuels to renewable energy, holds strategic potential for advancing the country s sovereign technological development. © 2024 RSC.